Pharmacokinetics of budesonide/glycopyrrolate/formoterol fumarate metered dose inhaler formulated using co-suspension delivery technology after single and chronic dosing in patients with COPD. (February 2020) - Dunn, Leonard J.; Kerwin, Edward M.; DeAngelis, Kiernan; Darken, Patrick; Gillen, Michael; Dorinsky, Paul
Abstract: Background: Budesonide/glycopyrrolate/formoterol fumarate metered dose inhaler (BGF MDI), formulated using co-suspension delivery technology, is a triple fixed-dose combination in late-stage clinical development for chronic obstructive pulmonary disease (COPD). Methods: We conducted two studies to characterize the pharmacokinetic (PK) profile of BGF MDI in patients with COPD: (i) a phase I, open-label, single and chronic (7-day) dosing study (NCT03250182) with one treatment arm (BGF MDI 320/18/9.6 μg); and (ii) a PK sub-study of KRONOS (NCT02497001), a phase III, randomized, double-blind study in which patients received 24 weeks' treatment with BGF MDI 320/18/9.6 μg, glycopyrrolate/formoterol fumarate (GFF) MDI 18/9.6 μg, budesonide/formoterol fumarate (BFF) MDI 320/9.6 μg, or budesonide/formoterol fumarate dry powder inhaler (BUD/FORM DPI) 320/9 μg. PK parameters in both studies included maximum observed plasma concentration (Cmax ) and area under the plasma concentration–time curve from 0 to 12h (AUC0–12 ). Results: In the phase I PK study (30 patients), budesonide and glycopyrronium Cmax were comparable after single and chronic dosing of BGF MDI (accumulation ratio [RAC ] 95% and 107%, respectively) whereas Cmax for formoterol was slightly higher after chronic dosing (RAC 116%). AUC0–12 for budesonide, glycopyrronium, and formoterol were higher following chronic versus single dosing, with an RAC of 126%, 179%, and 143%, respectively. After 7 days' dosing, AUC0–12 and Cmax for all three components of BGF MDI were similar to those in the KRONOS PK sub-study (202 patients) at Week 24. In the latter sub-study, Cmax and AUC0–12  at Week 24 were generally comparable across treatments for budesonide (geometric mean ratios [GMR] of 96%–109% for BGF MDI vs BFF MDI or BUD/FORM DPI), glycopyrronium (GMR of 88%–100% for BGF MDI vs GFF MDI), and formoterol (GMR of 80%–113% for BGF MDI vs GFF MDI or BFF MDI). Conclusions: Steady-state PK parameters of budesonide, glycopyrronium, and formoterol were similar after 7 days' dosing in the phase I PK study and after 24 weeks in the KRONOS PK sub-study. Systemic exposure to budesonide, glycopyrronium, and formoterol was generally comparable across treatments in the KRONOS PK sub-study, suggesting no meaningful drug–drug or within-formulation PK interactions.